Cost-Benefit Analysis (Cba) Of The Home Visit Program For Diabetes Mellitus Patients In The Prolanis Program at Clinics X And Y In Bogor Regency - Indah Yulistiawati; Prih Sarnianto; Nurita Andayani; Irmin Irmin (Publikasi Indonesia, 2025)
Research related to education through home visits was carried out to see medication adherence, blood sugar control and quality of life of DM patients as well as to measure the cost of re-admission the cost of referral to a hospital. To measure the costs and benefits (in rupiah) of an intervention and its effect on health care outcomes, pharmacoeconomics Cost Benefit Analysis was used. This comparative study used a cross-sectional design. The research sample was taken using purposive sampling technique as many as 30 from the group at the clinic implementing the home visit and 30 from the group at the non-home visit clinic. Measuring patient medication adherence using the Medication Adherence Report Scale (MARS-5) questionnaire, measuring the patient’s quality of life using the European Quality of Life 5 Dimensions (EQ-5D-5L) questionnaire. Blood sugar control data were obtained from medical records. For cost analysis, it was obtained from the SIM Medical Clinic and Primary Care BPJS Health. The results of the Mann-Whitney test showed a significant value (p>0.05). There was no significant difference in medication adherence and quality of life between the two groups. The OR value of 1.43 shows that the level of patient compliance in the clinic completing the home visit is 1.43 x higher than the patient at the non-home visit clinic. The value of OR 1 on blood sugar control indicates that both groups have the same chance of controlling blood sugar.